Formulation and performance of functional sub-micro CL-20-based energetic polymer composite ink for direct-write assembly. Issue 113 (28th November 2016) - Wang, Dunju; Zheng, Baohui; Guo, Changping; Gao, Bing; Wang, Jun; Yang, Guangcheng; Huang, Hui; Nie, Fude
Abstract : Direct writing deposition of energetic materials has been an area of interest for fuzing applications, novel initiation/booster trains, and for studying small scale detonations. Abstract : Direct writing deposition of energetic materials has been an area of interest for fuzing applications, novel initiation/booster trains, and for studying small scale detonations. Herein, we present a simple and efficient strategy to fabricate a high explosive ink formulation with good stability as well as excellent performance. Sub-micro CL-20 (2, 4, 6, 8, 10, 12-hexanitro-2, 4, 6, 8, 10, 12-hexaazaisowurtzitane) was prepared by the ball milling method and then mixed with an energetic binder consisting of GAP (glycidyl azide polymer binder) and N100 (polyisocyanate). The emulation curing process of GAP and N100 was illustrated by FT-IR spectra. Sub-micro CL-20 based ink shows wettability and good uniformity without cracks, porosity and voids. Moreover, the printed sample has lower sensitivity for impact heat stability than pure CL-20. A directly deposited sample in small grooves can provide steady detonation at a size of under 0.4 × 0.4 mm.